IMPLEMENTASI METODE WEBQUAL 4.0 DALAM MENGANALISIS KEPUASAN PENGGUNA WEBSITE SEARCH BUDDY - Tanriady, Eka Prasetyo; Munir, Abdul; Surasa, Hendra (STMIK KHARISMA Makassar, 2024)
Search Buddy is a website that provides service search services accessible through any platform. To consistently meet users' expectations of the website's services, an analysis of the website is essential. The conducted research aims to implement the WebQual 4.0 method in analyzing the quality and user satisfaction of the Search Buddy website. The WebQual 4.0 method is a framework that encompasses three main dimensions: usability quality, information quality, and service interaction quality. This method is considered suitable as it measures website quality from the perspective of end users. The analysis results indicate that the variables of usability quality and service interaction quality have a positive impact on user satisfaction. However, the information quality variable does not have a positive impact on user satisfaction. The coefficient of determination analysis shows that the variables of usability quality, information quality, and service interaction quality collectively influence user satisfaction by 40.3%. Based on these findings, it is recommended to pay attention to the aspects of usability quality and service interaction quality present on the website. Additionally, there is a need to enhance the quality of information presented on the website to make it more informative, relevant, and user-friendly, thereby potentially elevating user satisfaction with the Search Buddy website.